PERAN PEMBIAYAAN MURABAHAH DALAM MENINGKATKAN USAHA BATU BATA (STUDI PADA BMT AS-SALAM KANTOR KAS NGERECO KANDAT KEDIRI): (Studi Pada BMT As-Salam Kantor Kas Ngereco Kandat Kediri) - Anam, Muh Khoirul; Santoso, Haris (Islamic Economics Program, Faculty of Islamic Economics and Business, 2019)
Financial institutions are currently needed by all people because financial institutions are considered to be quicker in providing business capital loans. Previously, conventional banks were the only financial institutions operating in the financial sector or loans to the community before Islamic financial institutions, now with the development of financial institutions sharia society mostly prefers sharia finance rather than conventional, plus BMT which operates in the middle to lower class, this is what causes many people to take Islamic financial institutions because they prioritize family systems, so this study focuses on: 1). How is the application of murabahah financing at BMT As-Salam to brick businesses in the Ngreco Kandat Kediri village, 2). What is the role of murabahah financing at BMT As-Salam towards brick business in the Ngreco Kandat Kediri village, 3). How did the brick business increase in the Kandat Kediri Ngreco village after obtaining murabahah financing at BMT As-Salam. Research on the role of murabahah financing in brick business uses a descriptive qualitative approach with a type of case study research that refers to the interpretive postpositivistic thinking paradigm. The technique of collecting data is in-depth interviews, observation and documentation. The results of this study indicate that the application of murabahah financing at BMT As-Salam is very different where loans for business capital of bricks that should use mudharabah or musyarakah at BMT These salads use murabaha. Besides that the role of BMT As-Salam is very influential on brick business and before BMT As-Salam arrived, brick entrepreneurs still had difficulty finding capital to improve their business but after taking murabahah financing at BMT As-Salam, their efforts experienced an increase and prosperity life.